Glyph - Smith, Ali, 1962- (Pantheon, 2026)
From a literary master, a novel of ghosts and history and family legacy, of the unexpected acts of care that shine light into our dark. Ghosts don't exist. They don't. End of. Story, however. It is haunting. Everything tells it. It all starts when Petra and her little sister Patch hear a horrifying story from the past and find themselves making up a ghost. Is it imaginary? Is it real? Then it all starts again thirty years later when Petra, now estranged from Patch, finds a phantom horse kicking the furniture to pieces in her bedroom. What to do? She phones her sister. In a chiarascuro dance through our increasingly antagonistic era, Glyph asks if we're attending to the history that's made us and to the history we're making. A funny, warm and clear-eyed take on where we are now, Glyph is about what our imaginations are for and how, in a broken, brutal and divided time, we rekindle care, solidarity, resistance and openness. This anti-war novel, Ali Smith's most soulful, playful and vital yet, is a work of lightness that goes deep to counter the forces currently flattening the modern world.